Management of Isolated Local Failures Following Stereotactic Body Radiation Therapy for Low to Intermediate Risk Prostate Cancer - Aghdam, Nima; Pepin, Abigail N.; Creswell, Michael; Hsieh, Kristin; Smith, Clayton; Drescher, Nicolette; Danner, Malika; Ayoob, Marilyn; Yung, Thomas; Lei, Siyuan; Kumar, Deepak; Collins, Brian Timothy; et al. (Frontiers in Oncology, 2020)
Background: Stereotactic body radiation therapy (SBRT) is a safe and effective treatment option for patients with low to intermediate risk prostate cancer (1). SBRT results in very low PSA nadirs secondary to the delivery of high biologically effective doses. Studies reporting on the diagnosis, confirmation, and management of salvageable isolated local failures (ILF) are limited. This study aims to determine the incidence and management approach of ILF after SBRT in a large single institution cohort. Method: All patients with low or intermediate risk localized prostate cancer treated with SBRT at Georgetown University Hospital were eligible for this study. Treatment was delivered using robotic SBRT with doses of 35–36.25 Gy in five fractions. ILF were diagnosed using multiparametric MRI and/or biopsy prompted by rising PSA levels after achieving long-term nadir. Patient's characteristics were extracted from a prospective institutional quality of life trial (IRB 2009-510). Type of salvage therapy and post-salvage PSA were determined on subsequent follow-up and chart review. Results: Between December 2008 to August 2018, 998 men with low to intermediate risk prostate cancer were eligible for inclusion in this analysis. Twenty-four patients (low risk, n = 5; intermediate risk, n = 19) were found to have ILF within the prostate on either MRI (n = 19) and/or biopsy (n = 20). Median pre-treatment PSA was 7.55 ng/ml. Median time to diagnosis of ILF was 72 months (24–110 months) with median PSA at the time of ILF of 2.8 ng/ml (0.7–33 ng/ml). Median PSA doubling time was 17 months (5–47 months). Thirteen patients with biopsy proven ILF proceeded with salvage therapy (cryotherapy n = 12, HIFU n = 1). Of 12 patients who underwent cryotherapy, 7 had a post-treatment PSA of <0.1 ng/ml. One patient experienced a urethral-cutaneous fistula (grade 3 toxicity). Conclusion: The incidence of isolated local recurrence is rare in our cohort. Diagnosis and management of isolated local failures post-SBRT continues to evolve. Our report highlights the importance of early utilization of MRI and confirmatory biopsy at relatively low PSA levels and long PSA doubling time (1). Additionally, undetectable PSA levels after salvage therapy supports the role of early treatment in ILF (1). Further research is needed to determine appropriate patient selection and salvage modality in this population.